Heavy metals pollution and health risk in fish in Sungai Galas Kelantan, Malaysia - Baharom, Zarith Sufiani (2017)
A study on water surface and fish tissue for heavy metals concentrations was carried out at five sampling stations along Sungai Galas, Kelantan. Concentrations of heavy metals namely copper (Cu), zinc (Zn), lead (Pb), manganese (Mn) and nickel (Ni) were determined in the muscle, liver and gills of Hampala microlepidota (sebarau), Barbonymus schwanenfeldii (lampam sungai), Mystacoleucus obtusirostris (sia), Hemibagrus nemurus (baung) and Cyclocheilicthys apogon (temperas). The samples were collected by using gill nets during the wet (August to January) and dry seasons (February to September). The fish organs and water samples were analysed using Inductively Coupled Plasma- Mass Spectrometry (ICP-MS). The results of this study showed that the level of Zn, Cu and Pb concentrations at Dabong and Kuala Geris were higher in wet season when compared to dry season. There was positive correlation between heavy metal concentrations in fish tissues with heavy metal concentrations in water and physiochemical properties of water (p<0.05). The heavy metal concentrations found in muscles, liver and gills of all studied fish ranged from Cu: 0.30-0.39, Zn: 4.44-8.08, Pb: 0.17-0.51, Ni: 0.26-0.99, and Mn: 0.38-0.58 mg/kg wet weight; Cu: 2.19-6.16, Zn: 13.5-41.6, Pb: 2.06-7.14, Ni: 1.09-4.59, and Mn: 2.71-12.1 mg/kg wet weight, and Cu: 0.45-1.68, Zn: 10.49-40.99, Pb: 1.38-4.53, Ni: 1.25-5.75, and Mn: 8.81-44.11 mg/kg wet weight, respectively. The mean concentrations of Cu, Zn, Pb, Ni and Mn were significantly (p<0.05) different between fish organs and seasons. The liver samples showed highest levels of heavy metals compared to the gills and muscle. The Cu, Zn, Ni and Mn concentrations in liver and gills of M. obtusirostris were higher than other species. Muscles of H. macrolepidota (mg/kg wet weight) were found to have the highest concentrations of Zn (8.08-13.04) and Mn (0.41-0.58); while muscle of H. nemurus was detected having the highest concentration of Ni (0.72-1.67) and Pb (0.27-0.66). There was a positive correlation between Cu and Zn concentration in muscle with increasing weight and length of fish (p<0.05). The Pb concentrations at Gua Musang in muscles of B. schwanenfeldii, and C. apogon were generally higher than safety thresholds values recommended by Commission Regulation (EC, 2001) while concentrations of Pb at Gua Musang in H. nemurus exceeded the limit set by Food and Drug Administration, (USFDA, 1983), Food and Agriculture Organization (FAO, 2003) and EC (2001). Only Ni levels in C. apogon at Gua Musang did not exceed the limit stipulated by World Health Organization (WHO, 1985). All investigated metals in surface water (below 10 cm from surface) were significantly lower than the limits sets by WHO (2011) and class II National Water Quality Standards of Malaysia (NWQS), except for Pb which exceeded WHO (2011) and Class II NWQS standards, while Mn fell under Class III in NWQS. Total hazard quotient values indicated there was no public health hazard posed by consumption of the investigated fish species concerning all metals, for child and adult because the THQ is < 1.0.